Chemical bonding and band alignment at X2O3/GaN (X = Al, Sc) interfaces - Yuzheng Guo (Applied Physics Letters, 2019)
The chemical bonding and the band alignment at Al2O3/GaN and Sc2O3/GaN interfaces are studied using density functional supercell calculations. Using bonding models based on the electron counting rule, we have created the insulating interfaces with a small roughness and a clean bandgap. Ga-O bonds dominate the interfacial chemical bonding at both interfaces. The calculated band alignment agrees with the experimental values. For the Al2O3 interface, the calculated valence band offset is 1.17 eV using hybrid functionals, while that for the Sc2O3 interface is 0.81 eV. The conduction band offsets for both are larger than 1 eV, and is as large as ∼2 eV for the Al2O3 interface. The calculated band alignments indicate that Al2O3 and Sc2O3 are both suitable insulators for GaN-based MOSFET applications.